Characteristic length of the solidified melt pool in selective laser melting process. Issue 2 (20th March 2017) - Ahn, Il Hyuk; Moon, Seung Ki; Hwang, Jihong; Bi, Guijun
Abstract : Purpose: This paper aims to propose methods to evaluate the characteristic length of the melt pool for accurate fabrication and to identify the optimal process parameters in the selective laser melting process. Design/methodology/approach: Specimens with the types of the scans by controlling the degree of the overlap with hatch spacing are fabricated. The scan modes are classified by statistically analyzing the results of hardness tests. According to the classification of the scans, the evaluation methods are proposed based on the observation of the shape of the solidified melt pool. Findings: The control of the hatch spacing can reproduce all modes of the scan conditions, and hardness can be used to classify the scan modes. Originality/value: The proposed evaluation methods are based on the analysis of the experimental observation so that they can be easily used for the real evaluation.